Komunikasi Efektif dalam Pendidikan Anak Usia Dini Sebagai Teknik Meningkatkan Keterampilan Sosial dan Kognitif Anak - Nazwa Aliya; Waldo Venalosa Harianja; Vina Estella Kacaribu; Aman Simare-mare; Elya Siska Anggraini (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to explore effective communication strategies and techniques in early childhood education to improve children's social and cognitive skills. This research uses a qualitative descriptive approach with observation and interview methods, the research location was carried out at Harapan Islamiah Kindergarten. The results of the research show that effective communication can improve children's social skills such as the ability to communicate, interact and participate in the learning process. In addition, good communication can also effectively improve children's cognitive skills, such as critical thinking skills, analysis, and good social development. This research also shows that effective communication strategies and techniques used by teachers such as the use of clear language, giving examples, and have a big impact on social awareness. and children's emotions. This research shows that effective communication is important in early childhood education to improve children's cognitive and social skills.